PERBANDINGAN METODE KONVENSIONAL DENGAN BIM TERHADAP EFISIENSI BIAYA, MUTU, WAKTU - Rizal Maulana Rizqy; Nunung Martina; Hari Purwanto (Construction and Material Journal, 2021)
The construction field in Indonesia has been developing briskly. It can be proved by the discovery of the new method in the construction field, the Building Information Modelling (BIM) method. This BIM method is claimed to help finish the work more effective and less cost compare using the previous methods. It is because each application should be made manually and separately. Unlike the conventional method, the BIM method has the applications integrated into one, so it can accelerate the work progress and minimalize human resources. This research discusses the contrast of the construction planning process, especially when making the work method, and shop drawing, which reviewed from cost, quality, and time aspect. This research also examines the advantages and disadvantages of using the BIM method because it is categorized as a new method. The questionnaire and the interview method are used to collect the data. This research subject is the drafters and engineers already experienced in the construction field by applying the BIM method. The case of this study is Toll Road Jakarta – Cikampek II Selatan (Paket 3), with comparing the cost and time efficiency between conventional and BIM methods. The results show that the work will be done 43.82% faster using the BIM method than the conventional one. However, the required cost will be more expensive by using the BIM method because it will be allocated to invest in the software license. Keywords: Cost, Quality, and Time; Building Information Modelling (BIM); Conventional Methods.